Performance of Food Quality and Sensory Properties of Stick with Fortification of Fish Bone Flour Tuna and Kale Leaf Extract as Natural Food Coloran - Wardah; Rini Rahayu Sihmawati (Food Science and Technology Journal (Foodscitech), 2022)
Sticks are pastries that are generally made from wheat flour, tapioca and other starch sources with a high carbohydrate content, but low in nutrition so they need to be added or fortified with other nutrients such as sources of fat, protein, vitamins or minerals. Utilization of tuna bone waste can be an alternative as a fortificant in making sticks. In addition, fish bones also contain high protein and calcium. The use of kale leaf extract is also an alternative as a natural dye. This study aims to evaluate the increase in the nutritional value and preference of panelists for stick products fortified with tuna fish bone meal and kale leaf extract as natural dyes with a certain dose. The results of the chemical test showed that the stick product at P3 had the highest protein and calcium content compared to other treatments (P0, P1, P2) with a value of 6.61+0.11% protein content and 4.133+0.01 mg/100g calcium content. However, the water content and crispness of the product decreased, the water content of P3 was the lowest compared to other treatments (P1, P2 and P3) with a value of 0.945+0.12% while the highest hardness (using a penetrometer) was obtained at P3 of 6.17+0.11 mm/ 100g/10s compared to just 1.50+0.12mm/100g/10s on the P1. The results of the sensory test, the overall preference of the panelists, the aroma and color of the stick product, P2 (sticks fortified with 20% tuna bone meal and 15% natural dye of kale leaf extract) were significantly (P<0.05) higher than the P0 treatment. , P1, P3. The highest value of P2 was 43% for dryness, 40% for aroma, and 57% for color. However, organoleptic assessment of taste and texture, P0 (sticks without fortification of fish bone meal and kale leaf extract) was significantly (P<0.05) higher than treatments P1, P2, P3 but between treatments had no significant effect (P>0 ,05). The highest score of P0 is 40% for taste and 43% for texture. The more addition of fish bone meal and kale leaf extract, the protein and calcium content of the sticks increased, but the water content and crispness of the sticks decreased. For this reason, it is recommended that in producing sticks that are added with tuna fish bone meal and natural dye, kale leaf extract should use the best composition, which is sticks with the addition of 20% tuna fish bones and 15% kale leaf extract.